Short-term variation in aggregation and particulate organic matter under crops and pastures - Freibauer, A.; Westerhof, R; Ayarza, Miguel Angel; Silva, J.E. da; Zech, W. (International Center for Tropical Agriculture, 1999)
Short-term changes in soil aggregation, total and particulate organic C and N were studied in cropping and pasture systems of the Brazilian savannas, also known as the Cerrados. Furthermore, the concepts of a hierarchical aggregate structure and of the interaction of soil structure with particulate organic matter (POM) available for temperate soils were evaluated and modified for tropical Oxisols. The results showed that Oxisol peds (>2 mm) were sensitive to land use and subject to significant seasonal turnover, indicating a similar behavior as in temperate soils. Three POM fractions were distinguished: (1) free POM situated in the free soil pore space, (2) easily accessible POM, loosely bound in peds and introduced in this study, and (3) occluded POM, which was not studied. Free and easily accessible POMs were important active C pools and increased with human activity. The ratio of free to easily accessible POMs could clearly characterize the different land-use systems.